The Impact of Digital Currency on Global Trade : A New Frontier in International Accounting - Selvi Octapia Simatupang; Febry Valentin Zebua (Harmoni Economics: International Journal of Economics and Accounting, 2024)
The rise of digital currencies such as Bitcoin and Ethereum has reshaped the landscape of global trade and financial transactions. This study investigates how digital currencies are influencing international accounting practices, focusing on the challenges and opportunities posed by this disruptive technology. By analyzing case studies from major economies, the paper explores the potential for blockchain to enhance transparency, streamline cross-border payments, and ensure better tax compliance. The findings suggest that while digital currencies provide efficiency gains, they also introduce regulatory and volatility risks that must be managed by accounting professionals globally.